Tenosynovial Giant Cell Tumor Mimicking Acute Septic Arthritis of the Hip: A Case Report. (6th June 2022) - Honig, Evan; Harris, Andrew; Sabharwal, Samir; Levin, Adam; Honcharuk, Erin
Abstract : A 12-year-old boy presented to the pediatric emergency department with a 5-day history of atraumatic, progressively worsening right hip pain and inability to ambulate. He was afebrile and had elevated inflammatory markers (Erythrocyte Sedimentation Rate [ESR]: 42 mm/hr, C-Reactive Protein [CRP]: 6.6 mg/dL) with a normal white blood cell count of 6050 cells/mm 3 . Given the clinical concern for septic arthritis, joint aspiration of the right hip was done and demonstrated a bloody appearance with a WBC count of 54, 999 cells/mm 3 and RBC count of 7, 000 cells/mm 3 . MRI of the right hip demonstrated an intra-articular mass suggestive of tenosynovial giant cell tumor/pigmented villonodular synovitis. Subsequent biopsy and excision of the mass confirmed the diagnosis. The acute presentation of tenosynovial giant cell tumor with features mimicking septic arthritis is uncommon. This rare presentation of an already uncommon diagnosis should be considered in a child with an equivocal presentation for severe hip pain because misdiagnosis may lead to unnecessary or inadequately planned surgical treatment of the condition.